Analyzing Students’ Errors in Integral Calculus Through GeoGebra-Assisted Project-Based Learning - Diana Astria Gultom; Sahat Saragih; Edi Syahputra (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Students in higher education consistently demonstrate significant difficulties in integral calculus, particularly in selecting appropriate problem-solving strategies and executing procedural steps. Despite extensive research on mathematical errors, studies integrating Newman Error Analysis (NEA) with technology-enhanced, project-based pedagogy at the university level remain scarce. Objective: This research aims to examine the types of errors students make in solving integral problems in calculus by implementing Project-Based Learning (PBL) using GeoGebra software. Methods: The research adopted a descriptive qualitative method with 15 ACT students from the Informatics Department of Universitas Pelita Harapan Medan. Data were collected from written integral test items, observation sheets, and brief interviews with selected students. Errors made by students were classified according to the Newman Error Analysis (NEA) framework, which consists of reading, comprehension, transformation, process skill, and encoding errors. Results: The findings suggest that the combination of PBL with GeoGebra enables students to visualize integral concepts dynamically and enhances their geometric understanding of both definite and indefinite integrals. The most frequent error was transformation (60%), followed by process skill (53.3%), comprehension (46.7%), reading (20%), and encoding errors (13.3%). These results indicate that many students continue to struggle with deciding how to integrate an expression and completing the correct computations. The method helped alleviate conceptual difficulties owing to the visualization features of GeoGebra. Conclusion: GeoGebra-assisted PBL effectively supports error diagnosis and conceptual remediation in integral calculus. Integrating dynamic visualization with project-based inquiry reduces transformation and process skill errors by helping students connect symbolic procedures to geometric interpretations.